Assessment of the effects of anthropogenic activities on the El Arich groundwater using hydrogeochemistry, GIS and multivariate statistical techniques: A case study of the semi‐arid Kasserine region, Tunisia. Issue 4 (14th October 2021) - Nsiri, Madiha; Ben Brahim, Fatma; Khlifi, Mahmoud; Bouri, Salem
Abstract: With rapid urbanization and industrial development, waste discharges in west central Tunisia have multiplied. The focus here is on the waste manifestation from the National Company of Cellulose and Alfa Paper (SNCPA), which has been considered as a serious pollutant affecting natural resources as surface and groundwaters, human health and hygiene in the Kasserine land of semi‐arid climate. In order to preserve the quality assurance of available groundwater and determine its suitability for domestic an agricultural needs, a hydrogeochemical analysis was carried out to 30 samples for water samples taken from various source points of the study area (2018). This study attempt to assess the hydrogeochemical characteristics and ionic concentration with respect to WHO (2017) and Tunisian (NT.09.14) standards in the El Arich aquifer, in association with multivariate‐statistical‐analysis. Also DRASTIC model index was integrated with geographical information system (GIS) tools for the evaluation of the aquifer vulnerability to pollution. Results highlighted that only 17.65% of the groundwater samples are suitable for consumption purposes based on TDS, EC, Na +, K +, SO4 2–, and F – . The modeling of equilibrium geochemical processes elucidated that the groundwater's along flow‐paths are mostly in the oversaturated condition with respect to carbonate minerals, but they are undersaturated with evaporatic minerals. Based on some pre‐specified criteria and the validation by the water quality risk indices for soil salinization, the final vulnerability map shows four classes of vulnerability: very high, high, moderate, and low, depending on the intrinsic properties. HCA and FA suggest that high mineralization were related to rock‐water interactions and anthropogenic impact from the effluents discharged by the SNCPA. This multidisciplinary analysis would provide an overview for decision making authorities to take necessary action for the sustainable management and future planning in groundwater resource.